Upaya Promotif dan Preventif Kesehatan Mental Mahasiswa di PIK-R Syahid UIN Syarif Hidayatullah Jakarta - Retno Puji Rahayu; Nashcihah Nashcihah; Muhammad Masduki (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This research aims to find out what things must be done so that students with mental problems can be handled better, and what preventive and promotive efforts related to mental health have been carried out by the Information and Counseling Center for Martyred Youth at UIN Syarif Hidayatullah Jakarta. The method in this research uses qualitative methods. Qualitative data was obtained by conducting in-depth interviews and Focus Group Discussions (FGD) with informants selected purposively. The results of the research show that the conclusion of this research is that the Youth Information and Counseling Center (PIK-R) at UIN Syarih Hidayatullah Jakarta has organized promotional and preventive mental health efforts. Promotional and preventive mental health efforts that have been carried out include holding Genre Classes, Genre Goes to School Programs, Mentoring Activities, Free Online-Based Counseling Programs as well as holding various mental health seminar activities in the context of mental health promotion efforts.